Efektivitas Penggunaan Media Pembelajaran Di Sekolah TK Negeri Pembina Tilamuta Kabupaten Boalemo - Ahmad Hiola (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2022)
The purpose of this study was to determine the effectiveness of the use of learning media in Pembina Tilamuta Public Kindergarten school which is the First Public Kindergarten school at the district level and has always been an example for Kindergarten/KB schools in Boalemo Regency. This research is a qualitative research with descriptive qualitative methods using interview data collection techniques, documentation and triangulation. The subjects of this study consisted of six informants consisting of school principals, educators at Pembina Tilamuta Public Kindergarten, and Early Childhood Education Experts. The results of this study indicate that the use of learning media in Pembina Tilamuta Public Kindergarten is not effective in stimulating various aspects of development in children. This can be seen from the results of interviews which show that teachers are less creative in creating interesting learning media for children. The principal considers the teacher's motivation to be creative is very important in the success of the learning process. Minimal motivation to be creative makes the learning process in class monotonous and uninteresting. Keywords: effectiveness; learning media; teacher motivation; creation